(untitled) (Medical Forum Monthly, 2024)
Objective: To systematically evaluate the relationship between perceived stress and biochemical markers among nurses working in Intensive Care Units (ICUs) and their combined impact on physical and mental well-being. Study Design: Cross-sectional study Place and Duration of Study: This study was conducted at the Department Of Pathology of HBS Medical College and in the Intensive Care Units of HBS hospitals, Islamabad from 1st July 2023 to 10 February 2024. Methods: The study enrolled ICU nurses working under high-stress conditions. Perceived stress levels were measured using the Perceived Stress Scale (PSS-10), while biochemical markers, including salivary cortisol, heart rate variability, and inflammatory cytokines, were analyzed. Data on work hours, patient loads, and coping mechanisms were collected through structured questionnaires and medical records. Statistical analysis was performed to correlate stress levels with biochemical markers and assess their effects on nurses' health outcomes. Results: Nurses with higher perceived stress scores demonstrated significantly elevated levels of cortisol (mean: 26 ± 6 ng/mL) and inflammatory markers such as C-reactive protein (CRP) (mean: 4.9 ± 0.8 mg/L). A strong correlation was observed between perceived stress and disrupted heart rate variability (r = 0.67, p < 0.001). Adverse health outcomes, including fatigue, insomnia, and increased susceptibility to infections, were reported more frequently among nurses with higher stress and biomarker levels (p < 0.01). Conclusion: This study highlights the profound impact of perceived stress and its biochemical manifestations on the lives of ICU nurses. Interventions focusing on stress management, such as mindfulness programs and organizational support systems, are recommended to improve nurse well-being and enhance patient care quality.